SPE Annual Technical Conference and Exhibition 2011
DOI: 10.2118/146827-ms
|View full text |Cite
|
Sign up to set email alerts
|

Lower Quality Natural Quartz Proppants Result in Significant Conductivity Loss and Reduction in Ultimate Recovery: A Case History

Abstract: Progress in horizontal drilling and hydraulic fracturing techniques allow the oil and gas industry to get the most out of ultra tight, naturally fractured formations and unconventional reservoirs. The increasing price differential between crude oil and natural gas is resulting in unprecedented activity in the Bakken, Eagle Ford, Niobrara, and other oil rich shales. The industry is actively building drilling rigs and the fracturing companies are adding equipment and crews at an escalating rate to keep up with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In a paper presented by Syfan and Anderson (2011), six well conditions and proppant selection criteria were identified that influence obtainable conductivity. The six factors include closure stress, temperature, proppant concentration, proppant strength, proppant particle size, and proppant grain shape.…”
Section: Depth/closure Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…In a paper presented by Syfan and Anderson (2011), six well conditions and proppant selection criteria were identified that influence obtainable conductivity. The six factors include closure stress, temperature, proppant concentration, proppant strength, proppant particle size, and proppant grain shape.…”
Section: Depth/closure Stressmentioning
confidence: 99%
“…If nowhere else does size matter, it is in the business of selecting proppant for the long-term productivity of the well at hand (Syfan & Anderson 2011). The adage "bigger is better" is debatably true and is probably more likely.…”
Section: Proppant Particle Sizementioning
confidence: 99%
See 1 more Smart Citation